2010
DOI: 10.2337/dc09-0632
|View full text |Cite
|
Sign up to set email alerts
|

Truncal Pruritus of Unknown Origin May Be a Symptom of Diabetic Polyneuropathy

Abstract: OBJECTIVEOur goal was to ascertain the prevalence of pruritus in diabetic and nondiabetic subjects and the relevance of symptoms, signs, and nerve functions of diabetic polyneuropathy (DPN) of pruritus.RESEARCH DESIGN AND METHODSA large-scale survey of 2,656 diabetic outpatients and 499 nondiabetic subjects was performed. In diabetic subjects, the relationship between pruritus and age, sex, diabetic duration, A1C, Achilles tendon reflex (ATR), and abnormal sensation in legs was evaluated. In 105 diabetic subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
1
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 15 publications
(13 reference statements)
1
73
1
8
Order By: Relevance
“…For those patients, they related itching to loss of sudomotor function or direct C fiber injury (12). However, this explanation does not account for the case of polyneuropathy involving large myelinated fibers like our patient.…”
Section: Discussioncontrasting
confidence: 38%
“…For those patients, they related itching to loss of sudomotor function or direct C fiber injury (12). However, this explanation does not account for the case of polyneuropathy involving large myelinated fibers like our patient.…”
Section: Discussioncontrasting
confidence: 38%
“…The authors suggested that truncal pruritus of unknown origin was suspected of being a complication of diabetes, and diabetic polyneuropathy was suspected of being a possible origin of truncal pruritus of unknown origin. 20 To the best of our knowledge, in HD patients there is no study that compared the pruritus prevalence of diabetic and nondiabetic patients. As a novel finding, in this study we found that diabetic HD patients experienced more severe pruritus, as evaluated by VAS pruritus score, than nondiabetic HD patients and, interestingly, in both diabetic and nondiabetic patients, UP was independently related with HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…As the itching sensation is thought to be transmitted by small, unmyelinated sensory c-fibers, 27 pruritus may reflect some abnormality of the peripheral nerve. 20 Indeed, it was previously hypothesized that neuropathy seen in dialysis patients might reflect a dysfunction of the peripheral nervous system. 16,28 Additionally, as uremia progresses, peripheral nervous system becomes more affected, especially the sensory parts.…”
Section: Discussionmentioning
confidence: 99%
“…Entgegen der früheren Lehrmeinung ist Diabetes mellitus eine häufige metabolische Ursache, die zum generalisierten Pruritus führt. Typischerweise beginnt der "diabetogene Pruritus" an den Füßen/ Unterschenkeln oder am Rumpf [30]. Die Einstellung des postprandialen Glukosespiegels führt in der Regel zu einer Linderung des Pruritus [9].…”
Section: Pruritus Bei Kleinfaserneuropathieunclassified